Reinforcing Urea–Formaldehyde Resins with Low-Cost, Mechanically Derived Nanocellulose: A Sustainable Approach - Eleni A. Psochia; Emmanouil Karagiannidis; Eleftheria Athanasiadou; Konstantinos S. Triantafyllidis (Molecules)
In this work, we present the fabrication of low-cost, stable nanocellulose colloidal suspensions with an average particle size of approximately 160 nm, produced via a straightforward, solvent-free ultrasonication process that eliminates the need for corrosive chemicals or energy-intensive mechanical treatments. The resulting nanocellulose suspensions were utilized as reinforcing additives in urea-formaldehyde (UF) resins, which were subsequently applied in the production of particle boards. This approach addresses the increasing EU regulatory constraints regarding low formaldehyde-to-urea (F/U) molar ratios and the broader need for biobased, eco-friendly alternatives in the wood adhesive industry. Mechanical testing of the nanocellulose reinforced boards revealed notable improvements in the internal bond strength and modulus of rupture, along with a significant decrease in formaldehyde release compared to boards produced with conventional UF resins. These findings highlight the potential of ultrasonication-derived nanocellulose as an environmentally friendly, cost-effective additive to enhance the mechanical performance and reduce the environmental impact of UF-based wood composites.